2007
DOI: 10.1542/peds.2006-1083
|View full text |Cite
|
Sign up to set email alerts
|

Association of Apolipoprotein E Genotype and Cerebral Palsy in Children

Abstract: These data implicate the apolipoprotein E epsilon4 and epsilon2 genotypes as susceptibility factors in determining neurologic outcomes after perinatal brain injury. Additional studies are warranted to establish the role of apolipoprotein E in specific pathogenetic pathways leading to cerebral palsy or poor neurologic outcomes after perinatal brain injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
72
2
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(81 citation statements)
references
References 43 publications
5
72
2
2
Order By: Relevance
“…Previous studies have investigated factors such as intrauterine infection, (Nelson and Willoughby 2002;Wu 2002;Gibson et al 2006a) inherited thrombophilias (Gibson et al 2005) and cytokine polymorphisms (Gibson et al 2006b) as potential risk factors for cerebral palsy. Previous studies have suggested that polymorphisms in the Apolipoprotein E (APOE) gene may be associated with cerebral palsy (Meirelles Kalil Pessoa et al 2000;Kuroda et al 2007). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have investigated factors such as intrauterine infection, (Nelson and Willoughby 2002;Wu 2002;Gibson et al 2006a) inherited thrombophilias (Gibson et al 2005) and cytokine polymorphisms (Gibson et al 2006b) as potential risk factors for cerebral palsy. Previous studies have suggested that polymorphisms in the Apolipoprotein E (APOE) gene may be associated with cerebral palsy (Meirelles Kalil Pessoa et al 2000;Kuroda et al 2007). …”
Section: Introductionmentioning
confidence: 99%
“…No association has been found between APOE genotype and general cognitive ability (Turic et al 2001), autism (Raiford et al 2004) or spinal muscular atrophy (Morrison et al 1999). To date, there have been two smaller published studies on the relationship between APOE genotype and cerebral palsy, both implicating carriage of the 4 allele as a risk factor for cerebral palsy (Meirelles Kalil Pessoa et al 2000;Kuroda et al 2007). The 2 allele was also associated with an elevated risk for cerebral palsy in one of the studies (Kuroda et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Possession of the APOE e3 allele appears to be neuroprotective, while possession of the e4 allele is associated with deleterious health effects. In adults, the e4 allele predicts poorer outcomes and increased mortality following ischemic stroke and cardiopulmonary arrest, as well as an earlier age of onset of Alzheimer's disease (Eichner et al, 2002;possession of the e4 allele is associated with higher risk of and increased impairment in cerebral palsy (Kuroda et al, 2007). The mechanism by which APOE is thought to influence recovery from brain injury is not entirely clear, but it has been implicated in beta amyloid accumulation, oxidative stress response, inflammatory responses, growth and branching of neurites, glial activation, and excitotoxiticty ( Jofre-Monseny et al, 2008;Laskowitz and Vitek, 2007;Lynch et al, 2001;Miyata and Smith, 1996;Wang et al, 2007).…”
mentioning
confidence: 99%
“…This function is isoform-specific and the E4 isoform is less effective than E2 or E3 in attenuating the inflammatory response to brain injury [38] and systemic inflammation induced by lipopolysaccharide [39]. The increased risk for CP in carriers of the ε4 allele [8] is consistent with a mechanism in which a pre-or perinatal insult results in a CNS inflammatory response that may initially attenuate injury, but is not effectively regulated by the E4 protein.…”
Section: Editorial -Wainwrightmentioning
confidence: 84%
“…The combination of a delay in diagnosis and complexity of the mechanisms of neurologic injury in each disorder [4][5][6], are substantial impediments to progress in developing new therapies [7]. Data from a recent clinical study of genetic susceptibility to CP [8] conferred by the genotype of a gene, apolipoprotein E (APOE ), associated with risk of AD [9], suggest that the mechanisms of neurologic injury and potential therapeutic targets shared by the two conditions may be closer than previously appreciated. In this case-control study of children with CP and matched (by gender and race) controls, carriage of the ε4 allele increased the risk of CP by more than threefold.…”
mentioning
confidence: 99%